Existence of Nonoscillatory Solutions of First-Order Neutral Differential Equations - Božena Dorociaková; Anna Najmanová; Rudolf Olach (Abstract and Applied Analysis)
This paper contains some sufficient conditions for the existence of positive solutions which are bounded below and above by positive functions for the first-order nonlinear neutral differential equations. These equations can also support the existence of positive solutions approaching zero at infinity